Політичні події та соціальне життя Буковини у 1919 році - Піддубний, Ігор (Чернівці, Чернівецький університет, 2020)
Перший повоєнний рік для Буковини став часом повернення до мирного життя та вирішення цілого ряду проблем. Так, в межах організації адміністрування краєм виникли проблеми у підході до управління між двома міністрами делегатами, що мало результатом тривалий конфлікт. Складними були питання взаємин влади та населення, яке висувало певні претензії до користування майном. Нерідкими були прояви антисемітизму у діях місцевих мешканців. Проблема полягала і в організації та проведенні виборів до парламенту, які відбулися тільки наприкінці року. У статті зазначається, що Проявом невдоволення існуючою у війську ситуацією став виступ солдатів 113-го піхотного полку у Чернівцях, який доволі оперативно було придушено військовими підрозділами. Відновлення діяльності політичних організацій та загалом політичного життя в краї відбувалося в умовах стану облоги, що робило можливим здобуття успіху окремими політичними групами. Все ж у 1919 р. були вжиті заходи для зміцнення позицій нової влади і вибрані методи їх реалізації For Bukovyna year 1919 was a time of return to peaceful life. Although in those circumstances it proved to be a difficult task. Reunion of Bukovyna with Romania, accepted by Bukovyna General Congress had to be confirmed later at the Paris Peace Conference. That was the cause, which had created obstacles for carrying out parliamentary elections in the renewed country. Against this background, an important role was played by the organization of regional governance, which concerned the solution of a number of tasks. Food security, streamlining financial problems and restricting food smuggling remained important for the region. These tasks were solved by the ministers-delegates I. Flondor and I. Nistor. The activity of the two ministers-delegates led to an open conflict and their confrontation for a long time. The government crisis in Bukovyna, which was accompanied by the resignation of I. Flondor, led to his attempts to use German, Ruthenian, and Jewish political leaders in opposition to I. Nistor. The situation in the region was exacerbated by social demonstrations, actions of deserters in the region, manifestations of antisemitism. All this happened at a time when Bukovyna became a frontline zone, and military units of the VIII Division operated in Pokuttia. The authorities also noted a change in the mood of the population in this period, which could be a perception of the desired. The autumn of 1919 ended with the first parliamentary elections in conditions of siege, which were held on the basis of universal suffrage. Preparations for the elections took place in the conditions of confrontation between the political groups of I. Flondor and I. Nistor. In fact, in order to obtain seats in parliament and to organize the political forces of the Romanians of the region, I. Nistor and his supporters created the Democratic Party of Unification, which was able to win a seat in the Romanian parliament. Along with representatives of the Democratic Party of Unification, independent candidates were also elected. The opening of the newly elected parliament coincided with a rebellion of soldiers from the 113th Regiment in Chernivtsi, which was wrong accepted as a manifestation of Bolshevism. The situation in the region remained difficult at the end of 1919.
Political events and social life of Bukovyna in 1919
Keywords: Буковина; Я.Флондор; І.Ністор; повстання 113 полку; парламентські вибори 1919 р.; Bukovyna; I. Flondor; I. Nistor; uprising of the 113-th regiment; parliamentary elections of 1919